Ensaios destrutivos e não destrutivos em cordão de solda a gás inerte com eletrodo de tungstênio na fabricação de tanques de aquecedor solar com espessura de chapa reduzida - Coroa, Edgar Bergo (2023)
TIG welding processes are widely used to join metallic materials of different thicknesses, such as stainless steel. These are processes used in different segments of the industry, highlighting in the metallurgical area the linear and circumferential welding in pressure vessels applied in the solar heating system. Metallic tanks used for water storage are generally made of 304 or 316L stainless steel plates, calendered and welded using the TIG process. TIG welding parameters such as arc length, welding speed, gas flow and welding current are critical, influencing process characteristics such as: joint quality, profitability, welding cost, etc. Scientific articles from journals in the area of mechanical engineering, materials and welding metallurgy were reviewed. The main focus was to seek information about methods, processes and analyzes through material tests for characterizations of manual TIG welding in thin stainless steel plates. The main objective of this research is to develop an evaluation methodology through the characterization of the weld beads between the body and tops (manual welding) of Solis pressure vessels.